ENT600 : Calcaneus Entreprise (Tornado Electronic Hanger) / Muhammad Noor Adib Samsuddin … [et al.] - Samsuddin, Muhammad Noor Adib; Md Jafri, Muhammad Ezzat Emir; Mashri, Ahmad Faizal; Mohd Yusri, Mohamad Aiman Haiqarl (2016)
Tornado Hanger Electronic is a battery operated hanger that can dry clothes hanged on it. This product is very flexible as it can be used either using battery (wireless) or wired connection. Tornado Hanger is a low-power product as it can save electricity by using low voltage. The technologies used in this product are timer switch, charging plug, battery, general on/off switch, wheel and copper wiring.